Additional Diagnostic Value of Computed Tomography Perfusion for Detection of Acute Ischemic Stroke in the Posterior Circulation. Issue 4 (April 2015) - van der Hoeven, Erik J.R.J.; Dankbaar, Jan Willem; Algra, Ale; Vos, Jan Albert; Niesten, Joris M.; van Seeters, Tom; van der Schaaf, Irene C.; Schonewille, Wouter J.; Kappelle, L. Jaap; Velthuis, Birgitta K.
<x xml:space="preserve">Abstract</x> Background and Purpose— Detection of acute infarction in the posterior circulation is challenging. We aimed to determine the additional value of tomograpy (CT) perfusion to noncontrast CT and CT angiography source images for infarct detection and localization in patients suspected of acute ischemic posterior circulation stroke. Methods— Patients with suspected acute ischemic posterior circulation stroke were selected from the Dutch acute Stroke Trial (DUST) study. Patients underwent noncontrast CT, CT angiography, and CT perfusion within 9 hours after stroke onset and CT or MRI on follow-up. Images were evaluated for signs and location of ischemia. Discrimination of 3 hierarchical logistic regression models (noncontrast CT [A], added CT angiography source images [B], and CT perfusion [C]) was compared with C-statistics. Results— Of 88 patients, 76 (86%) had a clinical diagnosis of ischemic stroke on discharge and 42 patients (48%) showed a posterior circulation infarct on follow-up imaging. Model C (area under the curve from the receiver operating characteristic curve=0.86; 95% confidence interval, 0.77–0.94) predicted an infarct in the posterior circulation territory better than models A (area under the curve from the receiver operating characteristic curve=0.64; 95% confidence interval, 0.53–0.76; PC versus A<0.001) and B (area under the curve from the receiver operating characteristic curve=0.68; 95% confidence interval, 0.56–0.79; PC versus B<0.001). Conclusions— CT perfusion has significant additional diagnostic values to noncontrast CT and CT angiography source images for detecting ischemic changes in patients suspected of acute posterior circulation stroke.